2001
DOI: 10.1006/icar.2001.6662
|View full text |Cite
|
Sign up to set email alerts
|

Upper Limits on Gaseous CO at Pluto and Triton from High-Resolution Near-IR Spectroscopy

Abstract: Icarus 11, 503-513, we find a 3-σ upper limit to the CO mole fraction of 6%. For Pluto, this limit to the gaseous mole fraction argues against intimate mixtures (e.g., "salt-and-pepper" mixtures, as opposed to solid solutions) of surface CO and N 2 frost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 55 publications
0
20
1
Order By: Relevance
“…Pluto's atmosphere was first detected in 1988 during stellar occultation [ Elliot et al ., ] and has since been determined to be primarily composed of N 2 with minor abundance of CH 4 and CO, with surface pressures of ~17 microbar [ Young et al ., ]. Pluto's low gravity implies that a significant flux of atmospheric neutrals can escape [ Hunten and Watson , ; McNutt , ].…”
Section: Predictions For Solar Wind Interaction With Pluto's Atmospherementioning
confidence: 99%
“…Pluto's atmosphere was first detected in 1988 during stellar occultation [ Elliot et al ., ] and has since been determined to be primarily composed of N 2 with minor abundance of CH 4 and CO, with surface pressures of ~17 microbar [ Young et al ., ]. Pluto's low gravity implies that a significant flux of atmospheric neutrals can escape [ Hunten and Watson , ; McNutt , ].…”
Section: Predictions For Solar Wind Interaction With Pluto's Atmospherementioning
confidence: 99%
“…However, Young et al [1997] concluded that CH 4 is not the dominant atmospheric constituent. Young et al [2001] confirmed that CO is also a minor species, and concluded that, based on surface ice abundances, N 2 may be the dominant species (though no direct detection has been made). Pluto's low gravity implies that the atmosphere is only weakly bound and significant neutral escape rate can exist [ Hunten and Watson , 1982; McNutt , 1989].…”
Section: Introductionmentioning
confidence: 99%
“…Owen & Bar-Nun (1995), however, suggested that the likely maximum value for the initial N 2 /CO ratio cannot account for the currently observed N 2 dominance on Pluto. While the vapor pressure over multicomponent ices is not well understood, the composition of surface frost could be generally different from the underlying reservoir layer (Young et al 2001b). Presumably, the different volatility and/or the escape rate of N 2 and CO led to efficient concentration of N 2 in the surface frost through sublimation-recondensation.…”
Section: Discussionmentioning
confidence: 99%